Effects of Serum C-Peptide Level on Blood Lipid and Cardiovascular and Cerebrovascular Injury in Patients with Type 2 Diabetes Mellitus: A Meta-Analysis. (8th April 2022) - Qin, Juan; Sun, Rongli; Ding, Ding
Abstract : Objective . This study aims to investigate the effects of serum C-peptide levels on blood lipid and cardiovascular and cerebrovascular injury in patients with type 2 diabetes mellitus (T2DM). Methods . China National Knowledge Infrastructure (CNKI), WanFang Data, PubMed, Web of Science, and Embase databases were searched for relevant studies published from January 2010 to June 2021. All retrieved randomized controlled trials that evaluated the effect of serum C-peptide levels on blood lipids or cardiovascular and cerebrovascular injuries in T2DM patients were included in our study. Patients in the included studies were divided into normal C-peptide group (control group) and low C-peptide group (treatment group) according to fasting C-peptide levels. Meta-analysis was performed using Stata16.0. Results . A total of 7 studies were included for the meta-analysis. Compared with the control group, the treatment group was associated with a higher incidence of coronary heart disease (OR = 4.89; 95% CI: 1.13, 21.24; P < 0.05) and cerebral infarction (OR = 3.24; 95% CI: 0.59, 17.66; P < 0.05). In addition, patients in the treatment group had significantly higher levels of total cholesterol (SMD = 0.01; 95% CI: −0.38, 0.39; P < 0.05), triglyceride (SMD = 0.62; 95% CI: 0.24, 1.00; P < 0.05), glycated hemoglobin (SMD = 0.25; 95% CI: −0.50, 1.00; P < 0.05), and low-density lipoprotein cholesterol (SMD = 0.23; 95% CI: −0.00, 0.46; P < 0.05). However, there was no significant difference in high-density lipoprotein cholesterol levels between the two groups (SMD = 0.30; 95% CI: -0.26, 0.86; P > 0.05). Conclusions . Low serum C-peptide level significantly increases the incidence of coronary heart disease and cerebral infarction. Additionally, low serum C-peptide increases blood lipid level and promotes lipid deposition. Collectively, low serum C-peptide has a negative impact on the occurrence and development of T2DM and therefore serum C-peptide level needs to be adjusted timely.